PEMAHAMAN PERAN KELOMPOK USAHA BERSAMA SEBAGAI UPAYA PENGEMBANGAN EKONOMI KREATIF WISATA BAHARI - Handayani Handayani; Muhamad Ali Ulat; Endang Gunaisah; Ismail Ismail; Mustasim Mustasim; Muh Kasim; Hendra Poltak (Buletin SWIMP, 2022)
The joint business group is a strategy carried out in developing the creative economy of marine tourism in Malaumkarta. Development efforts are carried out by empowering the community through understanding the role of joint business groups. As many as 20 partners were empowered through interactive lectures and discussions. The results of the evaluation of the achievement of KUBe issues, strategies, problems and strengthening of KUBe were reached by 80%, the growth stage was reached by 75%, KUBe development was reached by 75%, work liaison system by 100%, and monitoring and evaluation published by 80% .